A method for improving the bonding strength of tantalum coating on the surface of biomedical peek material

By depositing Ti transition layer on the surface of PEEK material and alternately depositing Ta and Ti layers, the problem of insufficient bonding strength between PEEK material and tantalum metal coating is solved, and the bonding strength and biocompatibility of the coating are significantly improved.

CN119615095BActive Publication Date: 2025-04-18CHENGDU KENINGDA MATERIALS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510163523.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-18
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

In the prior art, the bonding strength between PEEK material and the tantalum metal coating is not high, resulting in the coating being prone to rupture and failure, affecting the stability and biocompatibility of biomedical materials.

Method used

Using magnetron sputtering method, a Ti layer is first deposited as a transition layer on the surface of PEEK material, and then a Ta layer and Ti layer are alternately deposited to form a functional coating structure of -(Ta-Ti)n-Ta, which enhances the binding force between the coating and the substrate.

Benefits of technology

Through this method, the bonding strength of the tantalum coating on the surface of PEEK material is significantly improved, the coating stress is reduced, the bone integration ability, cell adhesion and corrosion resistance are enhanced, and the service life of the coating is extended.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application relates to the field of biomedical materials, and specifically discloses a method for improving the bonding strength of tantalum coating on the surface of biomedical peek materials. The method adopts a magnetron sputtering method, with titanium target and tantalum target as target materials, first depositing a Ti layer as a transition layer on the surface of the peek material, and then alternately depositing a Ta layer and a Ti layer on the surface of the transition layer, so that a functional coating is formed on the surface of the transition layer, and the final material structure is: peek-Ti-(Ta-Ti) n ‑Ta, where n=1~3, the coating bonding strength is 40‑60 MPa. This method reduces the coating stress by constructing a Ti transition layer and a Ta‑Ti alternating coating on the surface of the peek material, thereby improving the bonding strength, stability and durability between the peek material and the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of biomedical materials, and more specifically, to a method for improving the bonding strength of a tantalum coating on the surface of a biomedical peek material. Background Art

[0002] Polyetheretherketone (PEEK) has been widely used in the biomedical field due to its modulus comparable to that of human cortical bone, radiolucency, high temperature durability, good sterilization, excellent chemical and biodegradability resistance, and excellent fatigue performance. These properties make PEEK an ideal material for manufacturing artificial joints, spinal implants, and other medical devices, greatly improving the success rate of surgery and the quality of life of patients. However, due to its biological inertness, low cell adhesion and protein absorption capacity on the surface, it has poor bone integration ability, which can prolong postoperative recovery time and even cause bacterial infection leading to implant failure.

[0003] In order to improve the surface properties of PEEK, the existing technical means mainly include using medical tantalum metal as a coating material. Its main advantages are that medical tantalum metal has good biocompatibility and can promote bone integration. At the same time, tantalum has good wear resistance and corrosion resistance. This coating method is usually achieved by physical vapor deposition (PVD), chemical vapor deposition (CVD) or electroplating.

[0004] Although the coating methods in the prior art can improve the surface properties of PEEK to a certain extent, the coating still faces the risk of cracking and failure due to the low bonding strength between the polymer and the metal coating and the large residual stress of the single-layer coating. Therefore, how to effectively improve the bonding strength between the PEEK substrate and the tantalum metal coating has become a key issue that needs to be solved in this field. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek materials.

[0006] This application adopts the following technical solutions:

[0007] In the first aspect, the present application provides a method for improving the bonding strength of a tantalum coating on the surface of a biomedical peek material, which adopts a magnetron sputtering method, uses a titanium target and a tantalum target as target materials, first deposits a Ti layer on the surface of the peek material as a transition layer, and then alternately deposits a Ta layer and a Ti layer on the surface of the transition layer, so that a functional coating is formed on the surface of the transition layer;

[0008] The structure of the functional coating is:-(Ta-Ti) n -Ta, where n=1~3;

[0009] The final material structure is: peek-Ti-(Ta-Ti) n -Ta, where n=1~3, the coating bonding strength is 40-60 MPa.

[0010] Furthermore, the outermost layer of the functional coating is a Ta layer with a thickness of 100-400 nm.

[0011] Furthermore, the structure of the functional coating is Ta-Ti-Ta-Ti-Ta.

[0012] Furthermore, in the functional coating, the thickness of a single Ti layer is 100-250 nm, and the thickness of a single Ta layer is 100-400 nm.

[0013] Furthermore, the method for improving the bonding strength of the tantalum coating on the surface of the biomedical peek material comprises:

[0014] (1) Installing the titanium target and the tantalum target in the magnetron sputtering equipment respectively;

[0015] (2) placing the peek material in a magnetron sputtering device, evacuating the device, and then filling it with argon gas to perform plasma treatment on the peek material;

[0016] (3) Magnetron sputtering coating is performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer;

[0017] (4) Continue to perform magnetron sputtering coating on the transition layer surface of the peek material, alternately depositing Ta layers and Ti layers until peek-Ti-(Ta-Ti) is formed. n -The final structure shown in Figure 1.

[0018] Further, the process of plasma treating the peek material includes:

[0019] Argon ions are used to bombard the material surface, the vacuum degree is 1-5 Pa, the cleaning time is 5-60 min, and the negative bias voltage is 50-500V.

[0020] Furthermore, the process parameters for depositing the Ti transition layer on the surface of the peek material include:

[0021] Vacuum degree 0.2-1Pa, coating time 5-30min, negative bias 30-200V, power 200-500W, target sample spacing 50-120mm, sputtering temperature 20-150℃.

[0022] Furthermore, the process parameters for alternately depositing the Ta layer and the Ti layer on the transition layer surface of the peek material include:

[0023] Vacuum degree 0.2-1Pa, coating time 1-60min, negative bias 30-200V, power 200-500W, target sample spacing 50-120mm, sputtering temperature 20-150℃.

[0024] Furthermore, the peek material keeps rotating during the DC magnetron sputtering process, with a rotation speed of 8r / min-12r / min.

[0025] Furthermore, the peek material is placed in a magnetron sputtering device and evacuated. Before the argon gas is filled, the vacuum degree is 3×10 -3 - 3.5×10 -3 Pa.

[0026] In summary, this application has the following beneficial effects:

[0027] 1. The method provided by the present application uses a magnetron sputtering method, with a titanium target and a tantalum target as target materials, to first deposit a Ti layer of a certain thickness on the surface of the peek material as a transition layer, and then alternately deposit a Ta layer and a Ti layer on the surface of the transition layer to form a functional coating, and finally form a -Ti-(Ta-Ti) on the surface of the peek material. n -Ta coating structure. Due to this structure of the coating, Ti is used as a transition layer, and then a thin Ta and Ti multilayer coating is constructed on its surface. On the one hand, the transition layer and multilayer coating reduce the coating stress, thereby improving the bonding strength between the peek material and the coating; on the other hand, Ti and Ta are both biocompatible and retain the advantages of Ta, improving the bone integration ability of the peek material, increasing cell adhesion, promoting cell growth, and accelerating the healing time.

[0028] 2. The present application can form a Ta-Ti repeating coating unit with specific structure and performance by alternately depositing Ta and Ti coatings. This structure not only has the excellent corrosion resistance, biocompatibility and wear resistance of the Ta coating, but also can optimize the overall performance of the coating by adjusting the ratio and distribution of Ta and Ti. At the same time, the alternatingly deposited Ta and Ti coatings can form a dense composite structure, which effectively prevents the penetration of corrosive media and biological fluids, not only improves the corrosion resistance of the coating, but also reduces the dissolution and shedding of the coating in biological fluids, thereby enhancing the stability of the coating. And when the outermost Ta layer fails, the remaining coatings can still function, and the durability is also improved.

[0029] 3. This application further improves the coating bonding strength by controlling the coating thickness, as well as the number and thickness of Ta-Ti repeating coating units in the functional coating. The Ti transition layer can effectively reduce the interface stress, and because the Ti transition layer can form a good bond with both the substrate peek material and the Ta coating, it acts as a bridge, thereby improving the bonding strength. The functional coating containing 1-3 Ta-Ti repeating coating units can further ensure that the coating can form sufficient mechanical bite force and chemical bonding force with the peek material, thereby improving adhesion.

[0030] 4. In this application, it is preferred to perform plasma treatment on the peek material before depositing the Ti transition layer. Under specific parameters, a large number of argon ions are generated to bombard the surface of the medical material, which can increase the surface active groups of the material, increase the surface energy, and enhance the bonding strength of the subsequent coating formed on the surface of the peek material. DETAILED DESCRIPTION

[0031] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0032] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0033] Example 1

[0034] This embodiment provides a method for improving the bonding strength of a tantalum coating on the surface of a biomedical peek material, which comprises the following steps:

[0035] The titanium target and the tantalum target are respectively installed on different targets in the magnetron sputtering equipment. The target size is φ76.2 mm×6 mm, and the magnetron power supply adopts a DC power supply.

[0036] The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in a magnetron sputtering instrument with an initial temperature of 18 °C and vacuumed to 3.5 × 10 -3 Pa, filled with argon. The peek material was plasma treated by bombarding the material surface with argon ions, vacuum degree 2Pa, cleaning time 10min, and negative bias voltage 500V;

[0037] Magnetron sputtering coating was performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.5 Pa, negative bias voltage 100 V, power 350 W, target sample spacing 80 mm, sputtering temperature 100 ° C, coating time 15 min, and the sample was rotated 360° during DC magnetron sputtering at a speed of 10 r / min.

[0038] Magnetron sputtering coating is continued on the surface of the transition layer of the peek material to alternately deposit Ta layers and Ti layers, and finally form a peek-Ti-Ta-Ti-Ta film layer structure.

[0039] Among them, the process parameters for depositing the Ta layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 350W, temperature 100℃, target sample spacing 80mm, time 20min; the process parameters for depositing the Ti layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 350W, temperature 100℃, target sample spacing 80mm, time 15min.

[0040] Example 2

[0041] This embodiment provides a method for improving the bonding strength of a tantalum coating on the surface of a biomedical peek material, which comprises the following steps:

[0042] (1) The titanium target and the tantalum target were respectively installed on different targets in the magnetron sputtering equipment. The target size was φ76.2 mm×6 mm, and the magnetron power supply used a DC power supply.

[0043] (2) The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in a magnetron sputtering apparatus with an initial temperature of 18°C ​​and vacuumed to 3.5×10 -3 Pa, filled with argon. The peek material was plasma treated by bombarding the material surface with argon ions, the vacuum degree was 1.5Pa, the cleaning time was 10min, and the negative bias voltage was 500V;

[0044] (3) Magnetron sputtering coating was performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.5 Pa, negative bias voltage 100 V, power 350 W, target sample spacing 80 mm, sputtering temperature 100 ° C, coating time 15 min. The sample was rotated 360° during DC magnetron sputtering at a speed of 10 r / min.

[0045] (4) Magnetron sputtering coating is continued on the surface of the transition layer of the peek material to alternately deposit Ta layers and Ti layers, and finally form a peek-Ti-Ta-Ti-Ta film layer structure.

[0046] Among them, the process parameters for depositing the Ta layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 350W, temperature 100℃, target sample spacing 80mm, time 30min; the process parameters for depositing the Ti layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 450W, temperature 100℃, target sample spacing 80mm, time 20min.

[0047] Example 3

[0048] This embodiment provides a method for improving the bonding strength of a tantalum coating on the surface of a biomedical peek material, which comprises the following steps:

[0049] The titanium target and the tantalum target are respectively installed on different targets in the magnetron sputtering equipment. The target size is φ76.2 mm×6 mm, and the magnetron power supply adopts a DC power supply.

[0050] The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in a magnetron sputtering instrument with an initial temperature of 18 °C and vacuumed to 3.5 × 10 -3 Pa, filled with argon. The peek material was plasma treated by bombarding the material surface with argon ions, vacuum degree 2Pa, cleaning time 10min, and negative bias voltage 500V;

[0051] Magnetron sputtering coating was performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.5 Pa, negative bias voltage 100 V, power 350 W, target sample spacing 80 mm, sputtering temperature 100 ° C, coating time 7 min, and the sample was rotated 360 ° during DC magnetron sputtering at a speed of 10 r / min.

[0052] Magnetron sputtering coating is continued on the surface of the transition layer of the peek material to alternately deposit Ta layers and Ti layers to eventually form a peek-Ti-(Ta-Ti)2-Ta coating.

[0053] Among them, the process parameters for depositing the Ta layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 350W, temperature 100℃, target sample spacing 80mm, time 20min; the process parameters for depositing the Ti layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 450W, temperature 100℃, target sample spacing 80mm, time 10min.

[0054] Example 4

[0055] This embodiment provides a method for improving the bonding strength of a tantalum coating on the surface of a biomedical peek material, which comprises the following steps:

[0056] The titanium target and the tantalum target are respectively installed on different targets in the magnetron sputtering equipment. The target size is φ76.2 mm×6 mm, and the magnetron power supply adopts a DC power supply.

[0057] The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in a magnetron sputtering instrument with an initial temperature of 18 °C and vacuumed to 3.5 × 10 -3 Pa, filled with argon. The peek material was plasma treated by bombarding the material surface with argon ions, vacuum degree 2Pa, cleaning time 10min, and negative bias voltage 500V;

[0058] Magnetron sputtering coating was performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.5 Pa, negative bias voltage 100 V, power 350 W, target sample spacing 80 mm, sputtering temperature 100 ° C, coating time 5 min, and the sample was rotated 360 ° during DC magnetron sputtering at a speed of 10 r / min.

[0059] Magnetron sputtering coating is continued on the surface of the transition layer of the peek material to alternately deposit Ta layers and Ti layers to eventually form a peek-Ti-(Ta-Ti)3-Ta coating.

[0060] Among them, the process parameters for depositing the Ta layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 350W, temperature 100℃, target sample spacing 80mm, time 10min; the process parameters for depositing the Ti layer are: vacuum degree 0.6Pa, negative bias voltage 100V, power 450W, temperature 100℃, target sample spacing 80mm, time 10min.

[0061] Example 5

[0062] This embodiment provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, which is different from embodiment 1 in that:

[0063] (2) The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in a magnetron sputtering apparatus with an initial temperature of 18°C ​​and vacuumed to 3.5×10 -3 Pa, filled with argon. The peek material was plasma treated by bombarding the material surface with argon ions, vacuum degree 1Pa, cleaning time 60 min, and negative bias voltage 50V.

[0064] Example 6

[0065] This embodiment provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, which is different from embodiment 1 in that:

[0066] The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in a magnetron sputtering instrument with an initial temperature of 18 °C and vacuumed to 3.0 × 10 -3 Pa, filled with argon. The peek material was plasma treated by bombarding the material surface with argon ions, vacuum degree 5Pa, cleaning time 5 min, and negative bias voltage 500V.

[0067] Example 7

[0068] This embodiment provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, which is different from embodiment 2 in that:

[0069] Magnetron sputtering coating was carried out on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 0.2 Pa, negative bias voltage 200 V, power 500 W, target sample spacing 120 mm, sputtering temperature 20 ° C, coating time 5 min, and the sample was rotated 360° during DC magnetron sputtering at a speed of 12 r / min.

[0070] Example 8

[0071] This embodiment provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, which is different from embodiment 2 in that:

[0072] (3) Magnetron sputtering was performed on the surface of the peek material after plasma treatment to deposit a Ti transition layer. The process parameters were: vacuum degree 1 Pa, negative bias voltage 30 V, power 200 W, target sample spacing 50 mm, sputtering temperature 150 °C, coating time 30 min. The sample was rotated 360° during DC magnetron sputtering at a speed of 8 r / min.

[0073] Example 9

[0074] This embodiment provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, which is different from embodiment 2 in that:

[0075] (4) Continue to perform magnetron sputtering coating on the transition layer surface of the peek material, alternately deposit Ta layers and Ti layers, and finally form a peek-Ti-Ta-Ti-Ta film structure. Among them:

[0076] The process parameters for depositing the Ta layer are: vacuum degree 0.2 Pa, negative bias voltage 200 V, power 500 W, temperature 150 °C, target-sample spacing 120 mm, time 5 min;

[0077] The process parameters for depositing the Ti layer are: vacuum degree 0.2 Pa, negative bias voltage 200 V, power 500 W, temperature 150 ° C, target sample spacing 120 mm, and time 2 min.

[0078] Example 10

[0079] This embodiment provides a method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, which is different from embodiment 2 in that:

[0080] (4) Continue to perform magnetron sputtering coating on the transition layer surface of the peek material, alternately deposit Ta layers and Ti layers, and finally form a peek-Ti-Ta-Ti-Ta film structure. Among them:

[0081] The process parameters for depositing the Ta layer are: vacuum degree 1Pa, negative bias voltage 30V, power 200W, temperature 20°C, target-sample spacing 50mm, time 60min;

[0082] The process parameters for depositing the Ti layer are: vacuum degree 1 Pa, negative bias voltage 30 V, power 200 W, temperature 20°C, target-sample spacing 50 mm, and time 20 min.

[0083] Comparative Example 1

[0084] The difference between this comparative example and the embodiment is that in this comparative example, a Ti transition layer is not deposited, and a peek-Ta coating is directly formed. The specific method is as follows:

[0085] The titanium target and tantalum target were installed on different targets in the magnetron sputtering instrument, with a target size of φ76.2mm×6mm, and a DC power supply was used for the magnetron power supply. The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in the magnetron sputtering instrument, with an initial temperature of 18°C, evacuated to 3.5×10-3Pa, and filled with argon. The plasma treatment process vacuum was 2Pa, the cleaning time was 10min, and the negative bias was 500V. No Ti transition layer was deposited, and a single-layer Ta coating was deposited. The Ta metal deposition process vacuum was 0.6Pa, the negative bias was 100V, the power was 350W, the temperature was 100°C, the target sample spacing was 80mm, and the time was 80min.

[0086] Comparative Example 2

[0087] The difference between this comparative example and the embodiment is that this comparative example forms a peek-Ti-Ta coating structure, and the specific method is as follows:

[0088] The titanium target and tantalum target were installed on different targets in the magnetron sputtering instrument, with a target size of φ76.2mm×6mm, and a DC power supply was used for the magnetron power supply. The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in the magnetron sputtering instrument, with an initial temperature of 18°C, evacuated to 3.5×10-3Pa, and filled with argon. The plasma treatment process vacuum was 2Pa, the cleaning time was 10min, and the negative bias was 500V. The transition layer Ti metal deposition process vacuum was 0.5Pa, the negative bias was 100V, the power was 350W, the temperature was 100°C, the target sample spacing was 80mm, and the time was 15min. Deposit a single layer of Ta coating, the Ta metal deposition process vacuum was 0.6Pa, the negative bias was 100V, the power was 350W, the temperature was 100°C, the target sample spacing was 80mm, and the time was 60min.

[0089] Comparative Example 3

[0090] The difference between this comparative example and the embodiment is that in this comparative example, a Ti transition layer is not deposited, and a peek-Ta-Ti-Ta coating is directly formed. The specific method is as follows:

[0091] The titanium target and tantalum target were installed on different targets in the magnetron sputtering instrument, with a target size of φ76.2mm×6mm, and a DC power supply was used for the magnetron power supply. The medical peek material washed and dried with anhydrous ethanol and deionized water was placed in the magnetron sputtering instrument, with an initial temperature of 18°C, evacuated to 3.5×10-3Pa, and filled with argon. The plasma treatment process vacuum was 1.5Pa, the cleaning time was 10min, and the negative bias was 500V. No Ti transition layer was deposited, and the Ta-Ti-Ta layer was deposited. The process vacuum of the Ta metal deposition process was 0.6Pa, the negative bias was 100V, the power was 350W, the temperature was 100℃, the target sample spacing was 80mm, and the time was 30min; the process vacuum of the Ti metal deposition process was 0.6Pa, the negative bias was 100V, the power was 350W, the temperature was 100℃, the target sample spacing was 80mm, and the time was 15min.

[0092] Performance Testing

[0093] Coating thickness test standard: Follow "GB / T 31563-2015 Metal Covering Thickness Measurement Scanning Electron Microscope Method" to test the film thickness of the sample.

[0094] Coating adhesion test standard: Test the samples in accordance with "YY / T 0988.11 Surgical Implant Coatings Part 11: Tensile Test Methods for Calcium Phosphate Coatings and Metal Coatings".

[0095] The results are shown in Table 1:

[0096] Table 1.

[0097] Membrane structure Ti transition layer thickness (nm) Functional coating single layer Ti layer thickness (nm) Functional coating single layer Ta layer thickness (nm) Total coating thickness (nm) Coating bonding strength (Mpa) Example 1 Peek-Ti-Ta-Ti-Ta 150 160 210 730 43 Example 2 Peek-Ti-Ta-Ti-Ta 150 220 340 1050 40 Example 3 <![CDATA[Peek-Ti-(Ta-Ti)2-Ta]]> 100 100 210 930 58 Example 4 <![CDATA[Peek-Ti-(Ta-Ti)3-Ta]]> 50 100 110 790 55 Comparative Example 1 Peek-Ta / / 900 900 14 Comparative Example 2 Peek-Ti-Ta 150 / 700 850 27 Comparative Example 3 Peek-Ta-Ti-Ta / 160 320 800 24

[0098] It can be seen from Table 1 that:

[0099] In comparative example 1, the same process was used to directly deposit a Ta layer on the peek surface, and the coating bonding strength was only 14Mpa. After further adding a Ti transition layer (i.e., comparative example 2), the coating bonding strength increased slightly. This shows that the presence of the Ti transition layer helps to reduce the interface stress and increase the bonding strength of the Ta layer.

[0100] It can be seen from Comparative Example 2 and Example 1-2 that, when a Ti transition layer is contained at the same time, the -Ta-Ti-Ta alternating layer contained in the coating structure has a significantly improved coating bonding strength compared to a single -Ta layer. At the same time, although Comparative Example 3 has a -Ta-Ti-Ta alternating layer, the coating bonding strength is still weak due to the absence of a Ti transition layer.

[0101] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for improving the bonding strength of tantalum coating on the surface of biomedical peek material, characterized in that: A magnetron sputtering method is adopted, with titanium target and tantalum target as target materials, a Ti layer is first deposited on the surface of the peek material as a transition layer, and then a Ta layer and a Ti layer are alternately deposited on the surface of the transition layer, so that a functional coating is formed on the surface of the transition layer; The structure of the functional coating is: -(Ta-Ti) n -Ta, where n=1~3; The final material structure is: peek-Ti-(Ta-Ti) n -Ta, where n=1~3, the coating bonding strength is 40-60MPa.

2. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 1, characterized in that: The outermost layer of the functional coating is a Ta layer with a thickness of 100-400 nm.

3. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 1, characterized in that: The structure of the functional coating is Ta-Ti-Ta-Ti-Ta.

4. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 3, characterized in that: In the functional coating, the thickness of a single Ti layer is 100-250 nm, and the thickness of a single Ta layer is 100-400 nm.

5. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 1, characterized in that: The method comprises: installing the titanium target and the tantalum target in the magnetron sputtering equipment respectively; The peek material is placed in the magnetron sputtering device, after evacuation, argon gas is filled in, and the peek material is subjected to plasma treatment; Performing magnetron sputtering coating on the surface of the peek material after plasma treatment to deposit a Ti transition layer; Magnetron sputtering coating is continued on the surface of the transition layer of the peek material, and Ta layers and Ti layers are alternately deposited until peek-Ti-(Ta-Ti) is formed. n -The final film structure shown in Figure 1.

6. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 5, characterized in that: The process of plasma treating the peek material includes: Argon ions are used to bombard the material surface, the vacuum degree is 1-5 Pa, the cleaning time is 5-60 min, and the negative bias voltage is 50-500 V.

7. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 5, characterized in that: The process parameters for depositing the Ti transition layer on the surface of the peek material include: Vacuum degree 0.2-1Pa, coating time 5-30min, negative bias voltage 30-200V, power 200-500W, target sample spacing 50-120mm, sputtering temperature 20-150℃.

8. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 5, characterized in that: The process parameters for alternately depositing Ta layers and Ti layers on the transition layer surface of the peek material include: Vacuum degree 0.2-1Pa, coating time 1-60min, negative bias 30-200V, power 200-500W, target sample spacing 50-120mm, sputtering temperature 20-150℃.

9. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 7 or 8, characterized in that: The peek material keeps rotating during the DC magnetron sputtering process, with a rotation speed of 8r / min-12r / min.

10. The method for improving the bonding strength of tantalum coating on the surface of biomedical peek material according to claim 5, characterized in that: The peek material was placed in the magnetron sputtering device and evacuated. Before filling with argon gas, the vacuum degree was 3×10 -3 -3.5×10 -3 Pa.

Citation Information

Patent Citations

  • Articular head with carbon basement membrane

    CN104984400A

  • Titanium-tantalum laminated composite adopting gradient structure and preparation method of titanium-tantalum laminated composite

    CN111569155A